2001
DOI: 10.1254/jjp.85.327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Noradrenergic and Serotonergic Antidepressants in Reducing Immobility Time in the Tail Suspension Test

Abstract: ABSTRACT-We examined the effects of two noradrenergic tricyclic antidepressants and two selective serotonin re-uptake inhibitors in the tail suspension test, with a suspension period of 30 min instead of the usual 10 min. Within the first 10 min, desipramine, nortriptyline and fluvoxamine significantly reduced the duration of immobility. Whereas desipramine and nortriptyline were also efficacious in the rest of the test period, fluvoxamine was not. Fluoxetine showed no significant effect throughout the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Against the NC-induced depressive behavioral alterations, significant antagonistic effects were provided by some antidepressants which inhibit the reuptake of monoamines and several CBs. However, unlike the IM group, the antidepressant drugs which inhibit the reuptake of monoamines (AT, CL, and FL) were not significantly effective in the NC group in the forced swimming test for these drugs could not be predicted based on the previous data and suggested a contribution of the monoamine system to the depression-related behavioral alterations in both forced swimming and tail suspension tests (Steru et al, 1985;Rénéric et al, 1998;Fujishiro et al, 2001). Nevertheless, considering the characteristic NC--tem in the forced swimming test, which include the alterations in dopamine levels (Tani et al, 1997;Renard et al, 2003), there seems to be a possibility that the antidepressants such as AT, CL and FL, which inhibit mainly the reuptake of noradrenaline and 5-hydroxy-tryptamine (5-HT), cannot antagonize effectively the NC-induced depressive swimming behaviors, at least during the test time, as compared to the other "antidepressant" drugs.…”
Section: Discussionmentioning
confidence: 92%
“…Against the NC-induced depressive behavioral alterations, significant antagonistic effects were provided by some antidepressants which inhibit the reuptake of monoamines and several CBs. However, unlike the IM group, the antidepressant drugs which inhibit the reuptake of monoamines (AT, CL, and FL) were not significantly effective in the NC group in the forced swimming test for these drugs could not be predicted based on the previous data and suggested a contribution of the monoamine system to the depression-related behavioral alterations in both forced swimming and tail suspension tests (Steru et al, 1985;Rénéric et al, 1998;Fujishiro et al, 2001). Nevertheless, considering the characteristic NC--tem in the forced swimming test, which include the alterations in dopamine levels (Tani et al, 1997;Renard et al, 2003), there seems to be a possibility that the antidepressants such as AT, CL and FL, which inhibit mainly the reuptake of noradrenaline and 5-hydroxy-tryptamine (5-HT), cannot antagonize effectively the NC-induced depressive swimming behaviors, at least during the test time, as compared to the other "antidepressant" drugs.…”
Section: Discussionmentioning
confidence: 92%
“…In the mouse-tail suspension test, the serotonergic antidepressant citalopram or imipramine, given 30 minutes before testing, interacted with acute nicotine to decrease immobility [13]. In the mouse tail suspension test, NE boosting tricyclic antidepressants, as well as the 5-HT boosting antidepressant fluvoxamine, reduced immobility when given 30 minutes before testing [14].…”
Section: Estimating Time Until Onset Of Drug Effect In Rodentsmentioning
confidence: 99%
“…Interestingly, fluoxetine (Prozac), a currently marketed clinically active antidepressant, has a similar profile to the CRF 1 receptor antagonists R121919 and DMP696 in the tail suspension and mouse forced swim tests. While, acute treatment with fluoxetine is often ineffective in the tail suspension test (e.g., Teste et al, 1993;Takeuchi et al, 1997;Wong et al, 2000;Fujishiro et al, 2001;Naudon et al, 2002;Nielsen et al, 2004) antidepressant-like activity has been observed after subchronic (Nielsen et al, 2004) and chronic treatment (Ukai et al, 1998;Naudon et al, 2002). Likewise, in the mouse forced swim test the ability to detect antidepressant-like activity with fluoxetine is enhanced when a chronic dosing paradigm is used (Dulawa et al, 2004).…”
Section: Chemical Name Companymentioning
confidence: 99%